Congenital diaphragmatic disease: An unusual presentation in adulthood. Case report. (2018) - Gurrado, Angela; Isernia, Roberta Maria; De Luca, Alessandro; Ferraro, Valentina; Virgintino, Daniela; Napoli, Anna; Cavallaro, Giuseppe; Maiorano, Eugenio; Pezzolla, Angela; Testini, Mario
Highlights: The diagnosis of congenital diaphragmatic disease in adulthood is rare. The correct development of the diaphragm is essential for the neighboring organs. A wrong detachment or migration of neural crest cell could cause diaphragm defects. Abstract: Introduction: Congenital diaphragmatic disease is a quite common condition that usually occurs in the neonatal period, and the diagnosis of congenital diaphragmatic disease in adulthood is rare. Case presentation: A 64-years-old Caucasian woman was admitted in emergency at our Department, due to a bowel obstruction and dyspnea. A CT-scan showed a diaphragmatic herniation in the left area, with malposition of dilated transverse and descending colon in the chest. An emergency laparatomy was performed, showing a toxic megacolon, in the absence of a true diaphragmatic hernia, and a left diaphragm and left liver hypoplasia. An intraoperative bronchoscopy revealed concomitant hypoplasia of the left lung. A subtotal colectomy with ileo-rectal anastomosis was performed. The postoperative course was uneventful. Histological examination demonstrated hyperplasia of the muscularis mucosae of the colon and cytoplasmic vacuolization of the Auerbach plexus ganglia . The karyotype genetic analysis excluded concomitant microdeletion or duplication syndromes. Discussion: To our knowledge, this seems to be the first reported case of toxic megacolon in a patient with congenital hypoplasia of the left bronchial-lung system, of the left liver, and of the left diaphragm. Conclusion: The correct development of the diaphragm is essential for the neighboring organs. The observed clinical pattern could be related to a partial modification of neural crest cell detachment or migration, which could be responsible for bowel and diaphragm defects, even though it was not included in typical neural crest cell syndromes. Further researches should be performed in order to define the sporadic or syndromic source of these multiorgan defects.